Empowering virtual collaboration: harnessing AI for enhanced teamwork in higher education - Akinul Islam Jony; Sultanul Arifeen Hamim (Academy of Cognitive and Natural Sciences, 2024)
The emergence of Artificial Intelligence (AI) has brought about a significant change in higher education. It has led to the adoption of more digitally advanced and collaborative models. This paper examines the potential of AI in promoting dynamic virtual teamwork and improving the collective experience in the academic world. It discusses how AI tools can be integrated into various sectors of virtual teamwork, such as academic learning, group projects, communication, assessment, research collaboration, administrative efficiency, engagement strategies, and continuous feedback mechanisms. The paper provides a comprehensive analysis of AI's role in these areas, showing how AI can personalize learning, facilitate complex group tasks, streamline communication, and provide real-time feedback. Ultimately, this will prepare students for the challenges of the professional world and enhance educational efficacy. The paper evaluates the significance of AI in each sector, offering insights into how higher education institutions can use these technologies to create an environment that fosters advanced virtual collaboration. The paper argues that strategic integration of AI is crucial in equipping students with the necessary skills and competencies for the evolving digital landscape of the 21st century.